MANIFESTATION OF THE ATTENTION CAPACITY AND THE LEADERSHIP SKILL DURING A PRACTICAL ACTIVITY IN STUDENTS - Bogdan-Constanti Rata; Marinela Rata (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The attention capacity is one of the cognitive sensory processes which are important in the process of professional training, influencing the quantity and quality of acquisitions and the formation of competences implicitly. A teaching career also requires leadership skills. The aim of this study is to assess the level of manifestation of attention and leadership skill in young students involved in the professional training process. In order to carry out this study, we applied an 'attention test' and a 'leadership skill test', both presented by Radu Nicolae 7 in 2007, on 100 students enrolled in the vocational training at the undergraduate level. Results show different levels of manifestation of attention, but also the inclusion of many students in the group with leadership skills, which help in the professional training.